IMPLEMENTASI PEMBELAJARAN MENDALAM (DEEP LEARNING) DALAM PEMBELAJARAN SENI MUSIK MATERI BUNYI DAN JENIS ALAT MUSIK DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Shintia Dona Armajuwita; Devano Andalas; Tulad Sutomo; Fifin Nabawiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Music learning in elementary schools requires an approach that goes beyond the memorization of musical terms and provides exploratory, reflective, and joyful experiences through which students develop conceptual understanding of sounds and musical instruments. This article aims to map research trends, implementation patterns, impacts, challenges, and opportunities of deep learning in elementary music education, particularly in the topic of sounds and types of musical instruments. The study employed a Systematic Literature Review (SLR) method by adapting the PRISMA 2020 principles. Literature was searched through Google Scholar, GARUDA, Crossref, DOAJ, and national journal portals, covering publications from 2024 to 2026. The selection criteria included topical relevance, connection to elementary education or music learning, full-text availability, and DOI clarity. Thematic synthesis was conducted on 16 core articles. The findings indicate that research on this topic has increased since 2024 and is dominated by interactive media development, project-based learning, game-based learning, the use of musical instruments, and conceptual studies on meaningful, mindful, and joyful learning. Deep learning implementation is reflected in activities such as observing sound sources, comparing timbre, classifying instruments, producing simple musical works, discussing, and reflecting on musical experiences. The most prominent impacts include improved engagement, conceptual understanding, creativity, collaboration, and learning motivation. The main challenges are limited availability of instruments, teacher readiness, diverse student musical abilities, and insufficient authentic assessment practices. This review recommends an elementary music learning model based on sound exploration, creative projects, simple digital media, and reflective learning as a direction for future research